2017
DOI: 10.3102/0002831217737028
|View full text |Cite
|
Sign up to set email alerts
|

How Readability Factors Are Differentially Associated With Performance for Students of Different Backgrounds When Solving Mathematics Word Problems

Abstract: Please cite as the following: Walkington, C., Clinton, V., & Shivraj, P. (2018). How readability factors are differentially associated with performance for students of different backgrounds when solving math word problems. AbstractThe link between reading and mathematics achievement is well known, and an important question is whether readability factors in mathematics problems are differentially impacting student groups. Using 20 years of data from the National Assessment of Educational Progress and the Trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 91 publications
0
18
0
2
Order By: Relevance
“…Previous research on the role of verbal skills has shown that linguistic features of word problems such as text length, word difficulty, or the role of pronouns can influence prototype word problem difficulty (Daroczy et al, 2015;Walkington et al, 2017). Mullis et al (2013) showed that this linguistic complexity primarily affected performance of students with lower reading abilities.…”
Section: Task Characteristics and Verbal Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on the role of verbal skills has shown that linguistic features of word problems such as text length, word difficulty, or the role of pronouns can influence prototype word problem difficulty (Daroczy et al, 2015;Walkington et al, 2017). Mullis et al (2013) showed that this linguistic complexity primarily affected performance of students with lower reading abilities.…”
Section: Task Characteristics and Verbal Skillsmentioning
confidence: 99%
“…Mullis et al (2013) showed that this linguistic complexity primarily affected performance of students with lower reading abilities. A simple explanation for this is that verbal skills increase in importance as linguistic complexity increases (Mullis et al, 2013;Walkington et al, 2017). Because complex word problems typically differ substantially in terms of the amount of text, the linguistic complexity, and the situational context of a task, there could be considerable differences in the influence of verbal skills between different complex word problems (Pongsakdi et al, 2020).…”
Section: Task Characteristics and Verbal Skillsmentioning
confidence: 99%
“…First, both linguistic and arithmetic factors (i.e., task characteristics) influence the accuracy (ACC) of a solution (e.g., Daroczy, Meurers, Heller, Wolska, & Nürk, 2020). Second, depending on individual characteristicslanguage abilities, mathematical abilities, intelligence, socioeconomic status which are differentially associated with performance (e.g., Walkington, Clinton, & Shivraj, 2018). Nevertheless, task characteristics and individual characteristics are not the only relevant factors; failures might originate from various sources (Ulu, Tertemiz, & Peker, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Which of these measures and dimensions are salient here? Of these five dimensions, Word Concreteness is the only one that aligns with the review items in this investigation, because this lesson content does not have narrativity, the syntactic form of items has no variability because the item format is standard across all of the items, and the items are too brief to exhibit referential or deep cohesion.Most Coh-Metrix investigations typically use long text portions, but a study byWalkington, Clinton, and Shivraj (2018) used Coh-Metrix measures of sentence-long mathematics word problems from 20 years of archived test data from the National Assessment of Educational Progress (NAEP). They used pilot studies to narrow down to four Coh-Metrix measures, specifically the Word Concreteness dimension plus three individual measures including word count, pronoun density, and presence of second person pronouns.…”
mentioning
confidence: 99%
“…403-404). FollowingWalkington et al (2018), this present investigation seeks to determine the influence of the Coh-Metrix item-level text measures on response confidence using two of these measures, word count and Word Concreteness. Note that pronoun density and presence of second person pronouns used by Walkington et al could not be considered because the review items in this present investigation contain only three pronouns.…”
mentioning
confidence: 99%